Some biological aspects of the golden hind grouper (Cephalopholis aurantia) harvested in the northern coast of Aceh, Indonesia (a preliminary study). Issue 1 (February 2021) - Fadli, N; Damora, A; Muchlisin, Z A; Dewiyanti, I; Ramadhaniaty, M; Hanif, A; Zahara, C S; Rusdi, M; Nur, F M; Batubara, AS; Siti-Azizah, M N
Abstract: Cephalopholis aurantia is one of the grouper species considered as the least concern (LC) based on the IUCN category. However, the data related to its biological features is limited. The present study's objective was to study some biological aspects of the golden hind grouper harvested in the northern coast of Aceh. The fishes were collected from June - August 2020 in several fish landing sites (TPI) and fish market located in Banda Aceh and Aceh Besar district. In total, 24 fish specimens were collected in this study. All samples were small and young (between 103.1-240.0 mm TL and 60.6-267.5 g). In addition, all the collected fishes were female with the gonad maturity levels varied from stage I to stage IV with the gonad weight ranged from 0.01-2.00 gr. This study is providing baseline data of some biological aspects of the golden hind grouper that will be valuable in developing a practical fisheries management of the species.